Pengaruh Layanan Frontliner dan Relationship Marketing Terhadap Loyalitas Nasabah pada Bank Muamalat Indonesia Kantor Cabang Pembantu Madiun - Imanurrovi, Fithrotul; Himmati, Risdiana (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2023)
Competition between Islamic banks and conventional banks in gathering customers to use their products is getting tougher. Islamic banks, especially Bank Muamalat Indonesia KCP Madiun, also continue to improve their services in order to retain customers. For Bank Muamalat Indonesia KCP Madiun, the existence of loyal customers is very important because it can describe the level of profitability and the company's image in the public. With good service quality, full trust from customers, close commitment, good communication, and appropriate handling of problems, of ourse Bank Muamalat Indonesia KCP Madiun will be increasingly favored by its customers. This study aims to (1) determine the effect of frontliner service on customer loyalty at Bank Muamalat Indonesia KCP Madiun. (2) determine the effect of relationship marketing on customer loyalty at Bank Muamalat Indonesia KCP Madiun. (3) determine the effect of frontliner services and relationship marketing together on customer loyalty at Bank Muamalat Indonesia KCP Madiun. This research method is quantitative, with the type of associative research. Data collection techniques using a questionnaire. The results of this study can be concluded that (1) frontliner service has a positive and not significant effect on customer loyalty at Bank Muamalat Indonesia KCP Madiun because the frontliner service value is smaller than the t table value, namely 1.383 <1.693 and a significance value of 0.176 > 0.05, (2) relationship marketing has a positive and significant effect on customer loyalty at Bank Muamalat Indonesia KCP Madiun with a relationship marketing value greater than the t table value of 2.742 > 1.693, and a significance value of 0.009 <0.05, (3) frontliner services and relationship marketing together positive and significant effect on customer loyalty of Bank Muamalat Indonesia KCP Madiun with Fcount of 10.394 > Ftable 3.30 and a significance value of 0.000332 <0.05.